THE INFLUENCE OF GENOTYPE, SOIL TILLAGE AND FERTILISATION ON CARBON SEQUESTRATION IN MAIZE - Elena PETCU; Cătălin LAZĂR; Elena PARTAL; Laura CONŢESCU; Daniela HORHOCEA (Journal of Applied Life Sciences and Environment)
The increase in the concentration of greenhouse gases in the Earth’s atmosphere, especially that of CO2, is a major concern because it is the main source leading to global warming, and its impact on climate change is still widely studied. The intensity and frequency of drought and flooding increase due to the change in climate, which has a negative impact on crop productivity and food security. The aim of this paper was to demonstrate the role of corn in carbon sequestration based on plant biomass and soil organic carbon accumulation. We presented the main factors that contribute to carbon sequestration and concrete examples regarding the capacity of corn hybrids created at National Agricultural Research and Development Institute (NARDI) Fundulea, as well as aspects regarding the importance of soil tillage and fertilisation. In contrast to genotypes in which this ratio was lower, maize genotypes that demonstrated a rise in the root:stem ratio under drought stress conditions produced more biomass, suggesting that the roots of these genotypes can grow at water potentials where stem growth is inhibited, which are attributes that also prove their good potential for carbon sequestration under climate change conditions. The organic carbon content in the superficial soil layer decreased with the intensification of the degree of soil mobilisation (9.95% when working the soil with the chisel, 17.91% for ploughing), but fertilisation had a beneficial effect. The biomass was higher than that of the unfertilised soil. This means that a higher carbon input has a positive influence on the carbon stock in the soil.